Death, TIR, and RHIM: Self-assembling domains involved in innate immunity and cell-death signaling. Issue 2 (5th December 2018) - Nanson, Jeffrey D; Kobe, Bostjan; Ve, Thomas
Abstract: The innate immune system consists of pattern recognition receptors (PRRs) that detect pathogen- and endogenous danger-associated molecular patterns (PAMPs and DAMPs), initiating signaling pathways that lead to the induction of cytokine expression, processing of pro-inflammatory cytokines, and induction of cell-death responses. An emerging concept in these pathways and associated processes is signaling by cooperative assembly formation (SCAF), which involves formation of higher order oligomeric complexes, and enables rapid and strongly amplified signaling responses to minute amounts of stimulus. Many of these signalosomes assemble through homotypic interactions of members of the death-fold (DF) superfamily, Toll/IL-1 receptor (TIR) domains, or the RIP homotypic interaction motifs (RHIM). We review the current understanding of the structure and function of these domains and their molecular interactions with a particular focus on higher order assemblies. We review the structure and function of domains involved in signaling by cooperative assembly formation (SCAF) in innate immunity and cell-death pathways.